Analýza součinnosti subjektů činných při hromadném narušení veřejného pořádku - Petržilka, Jiří; Petržilka Jiří (České vysoké učení technické v Praze, 2018)
Má diplomová práce se zabývá hromadným narušením veřejného pořádku z pohledu Policie České republiky. Mezi cíle práce patří popis typizovaných činností Policie České republiky a spolupráce jednotek Policie ČR na místech s hromadným narušením veřejného pořádku. Hlavním výstupem práce je návrh nového opatření, které by bylo možné použít při hromadném narušení veřejného pořádku. V diplomové práci byla použita metoda komparace, která srovnává legislativu České republiky a Velké Británie v problematice hromadného narušení veřejného pořádku. Další metodou, která byla použita, byl řízený rozhovor s bývalým a současným příslušníkem Policie České republiky a dotazníkové šetření, zaměřené na názor civilního obyvatelstva na problematiku hromadného narušení veřejného pořádku.

My diploma thesis deals with the mass violation of public order from the point of view of the Police of the Czech Republic. The objectives of the thesis include description of typified activities of the Police of the Czech Republic and co-operation of the units of the Police of the Czech Republic in places with mass disruption of public order. The main output of the work is the draft of a new measure that could be used in the case of mass disruption of public order. The comparative method was used in the diploma thesis, which compares the legislation of the Czech Republic and Great Britain in the issue of the mass violation of public order. Another method used was a controlled interview with a former member and one a member of the Police of the Czech Republic and a questionnaire survey focused on the opinion of the civilian population on issues of mass disruption of public order.
Analysis of the Cooperation of Subjects Acting in Mass Violation of Public Order
Keywords: Policie České republiky,hromadné narušení veřejného pořádku,veřejný pořádek,sportovní utkání,demonstrace; Policie of the Czech Republic,mass disruption of public order,public order,sports matches,demonstration